2008
DOI: 10.1523/jneurosci.2897-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

Rescue of Neurons from Ischemic Injury by Peroxisome Proliferator-Activated Receptor-γ Requires a Novel Essential Cofactor LMO4

Abstract: Activation of peroxisome proliferator-activated receptor-␥ (PPAR␥) signaling after stroke may reduce brain injury, but this effect will depend on the levels of receptor and cofactors. Here, we showed that the direct effect of PPAR␥ signaling to protect neurons from ischemic injury requires a novel cofactor LMO4, because this effect was lost in LMO4-null cortical neurons. PPAR␥ agonist also failed to reduce cerebral infarction after transient focal ischemia in CaMKII␣Cre/LMO4loxP mice with LMO4 ablated in neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 43 publications
1
36
0
Order By: Relevance
“…LMO4 is a small protein (165 aa) that contains two protein-interacting LIM domains. LMO4 serves not only as a cofactor of many transcription factors (Manetopoulos et al, 2003;Kashani et al, 2006;Schock et al, 2008), but also interacts with transmembrane receptors to modulate their signaling (Novotny-Diermayr et al, 2005;Bong et al, 2007). Whether LMO4 couples signals from membrane receptors to changes in gene expression is not known, although we showed that LMO4 is present in the cytoplasm and nucleus, and translocates from the cytoplasm to the nucleus in response to extracellular stimuli (Chen et al, 2007a).…”
Section: Introductionmentioning
confidence: 79%
“…LMO4 is a small protein (165 aa) that contains two protein-interacting LIM domains. LMO4 serves not only as a cofactor of many transcription factors (Manetopoulos et al, 2003;Kashani et al, 2006;Schock et al, 2008), but also interacts with transmembrane receptors to modulate their signaling (Novotny-Diermayr et al, 2005;Bong et al, 2007). Whether LMO4 couples signals from membrane receptors to changes in gene expression is not known, although we showed that LMO4 is present in the cytoplasm and nucleus, and translocates from the cytoplasm to the nucleus in response to extracellular stimuli (Chen et al, 2007a).…”
Section: Introductionmentioning
confidence: 79%
“…Recent studies have shown that both rosiglitazone and pioglitazone are neuroprotective in animal models of acute focal ischemia. 3 Studies have also shown that neuroprotection by TZDs following ischemia may involve: (a) a reduction in the inflammatory response, such as by upregulation of nuclear factor-kB, intercellular adhesion molecule-1, or cyclooxygenase; [16][17][18][19] (b) activation of an anti-inflammatory mediator, such as synthesis of lipoxin A 4 by 5-lipoxygenase expression; 20 (c) activation of superoxide dismutase; 21,22 or (d) prevention of harmful neuronal responses to ischemic insult, such as enhanced 14-3-3e expression. 23 There is significant evidence from these studies that PPARg activation is involved in neuroprotection.…”
Section: Discussionmentioning
confidence: 99%
“…We showed previously that signals like extracellular ATP, hypoxia, and depolarization stabilize LMO4 mRNA and protein [11,18,19]. Ablation of LMO4 increases neuron susceptibility to ischemic injury, resulting in a larger infarction in an experimental model of stroke [11].…”
Section: Introductionmentioning
confidence: 91%
“…LMO4 interacts with transcription factors, including LIM homeodomain proteins, basic HelixLoop-Helix (bHLH) proteins, peroxisome proliferator-activated receptor gamma (PPARγ), and cAMP response element-binding protein (CREB), to activate gene expression in the nervous system [11][12][13][14][15]. Germline deletion of LMO4 leads to embryonic lethality and failure of the cranial neural tube to close, resulting in exencephaly [16,17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation